Pseudocarcinomatous changes in giant porokeratosis of mibelli’: Histopathology as a valuable asset for early recognition of neoplastic changes – A case report with review - Sushantika, Sushantika; Gupta, Sunil Kumar (Indian Journal of Case Reports, 2020)
Porokeratosis is defined as a rare disorder of keratinization caused by clonal expansion of keratinocytes and characterized by an expanding thread-like border of hyperkeratotic plaques or papules with atrophic center. It is a genetically heterogeneous disorder that is mostly inherited as autosomal dominant trait. It is characterized histologically by the presence of a thin column of parakeratotic cells “cornoid lamella” representing the active border. This is a case report of a patient suffering from giant porokeratosis of Mibelli who developed secondary changes over the lesion in due course of time arousing suspicion of malignancy which turned out to be benign histopathologically. The risk factors for malignant changes are usually persistence of the lesion for long time, radiation therapy, long-term exposure to ultraviolet radiation, electron beam therapy, and immunosuppression associated with malignancies such as lymphoma, HIV infection, or due to immunomodulatory drugs.